Fatty Acids of Erythrocyte Membranes and Blood Serum as Possible Predictors of Exacerbation in Patients with Inflammatory Bowel Diseases - M. V. Kruchinina; M. F. Osipenko; A. I. Valuyskikh; E. Yu. Valuiskikh; I. O. Svetlova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to study the levels of fatty acids in the membranes of erythrocytes and blood serum in patients with inflammatory bowel diseases (IBD) examined over time, as possible predictors of exacerbation of the disease.Materials and methods. Over a period of 6–12 months, 24 patients (mean age — 38.2 ± 4.4 years) with IBD with of moderate and mild severity of the disease were examined, of which 10 patients had ulcerative colitis, 10 — Crohn’s disease, 4 — unclassified colitis: the first examination was in the acute stage, the second was in the remission stage. In 48 additionally examined patients with IBD in remission (25 patients with ulcerative colitis, 15 — with Crohn’s disease, 8 — with unclassified colitis), the course of the disease was monitored over the next 12 months. The comparison group included 53 people comparable to the main groups in age. The study of the composition of fatty acids (FAs) in the membranes of erythrocytes and blood serum was carried out using a gas chromatograph mass spectrometry system based on three quadrupoles Agilent 7000B (Agilent Technologies Inc., USA).Results. In the acute stage, patients with IBD have a higher total content of saturated fatty acids (SFAs) in erythrocyte membranes compared to the control group (p = 0.006), and, on the contrary, lower levels of unsaturated fatty acids (UFAs) (p = 0.005), mainly due to polyunsaturated FAs (PUFAs) (p = 0.026), namely omega-6 PUFAs (p = 0.011).Remission of IBD is associated with an increase in the level of a number of SFAs in the blood serum — margaric C17:0 (p = 0.024), arachidic acid (C20:0) — in erythrocyte membranes and serum (p = 0.0001 and p = 0.019, respectively), with a decrease in the total content of monounsaturated FAs in erythrocyte membranes (p = 0.022), an increase in the total concentration of PUFAs due to both omega-3 PUFAs (p = 0.0008) and omega-6 PUFAs (p = 0.033) in erythrocyte membranes compared with a group of healthy individuals.The exacerbation stage in patients with IBD examined over time is associated with higher levels of stearic FA C18:0 (p = 0.005), SFA/UFA (p = 0.034) and SFA/PUFA (p = 0.039) ratios in erythrocyte membranes, serum level of arachidic FA C20:0 (p = 0.008), and, on the contrary, lower content of UFAs in erythrocyte membranes — eicosapentaenoic C20:5n-3 (p = 0.0023), eicosadienoic C20:2n-6 (p = 0.0027), hexadecadienoic C16:2n-6 (p = 0.006), docosatetraenoic C22:4n-6 (p = 0.008) and alpha-linolenic C18:3n-3 (p = 0.039).A combined “panel” of fatty acids, including the levels of C20:2n-6, C18:0 in erythrocyte membranes and the content of C20:0 in blood serum, provided an AUC of 0.683 (95 % CI: 0.500–0.844), sensitivity 91.4 %, specificity 68.3 %.Levels of C20:5n-3, C20:2n-6, C18:0, C16:2n-6, C22:4n-6, C18:3n-3 fatty acids, SFA/UFA and SFA/PUFA ratios in erythrocyte membranes and content C20:0 in blood serum, used as biomarkers — predictors of the development of exacerbation in patients with IBD who were in remission, predicted the development of exacerbation of IBD after 2–4 months in the case of maximally changed levels of FAs, after 6–8 months — with moderately changed levels FAs, maintaining remission for 12 months — with minimally changed FAs levels.Conclusion. Fatty acids of erythrocyte membranes and blood serum should be considered as promising markers for further studies related to the diagnosis and prediction of exacerbation in IBD.